Mycotoxins and Food Safety Recent Advances - Alina Marc, Romina (IntechOpen, 2022)
Global food security is a major issue worldwide. Given the rapid socioeconomic changes of the last decade, food processing, food supply, and consumption patterns have undergone significant changes, increasing the number of food security problems. One of these problems is mycotoxin contamination, which can have major adverse effects on food safety and crop yield. This book presents comprehensive information on recent advances in mycotoxins and food safety. It includes five sections: "Introduction: Mycotoxins and Food Safety Overview"; "The Influence of Contaminants on Food Safety" "Mycotoxins in Feed"; "Indirect Mycotoxin Contamination of Food Safety"; and "Control and Reduction of Mycotoxin Contamination".